TINJAUAN YURIDIS PERJANJIAN PENGANGKUTAN CRUDE PALM OIL (CPO) ANTARA PT. MOPOLI RAYA DENGAN PT. MEGA NUSANTARA ABADI (STUDI DI PT. MOPOLI RAYA) - SHELLA DWI AULINA (University of North Sumatera, 2018)
Transportation as a contract always preceded by an agreement between the carrier and the sender. In the transportation contract, the carrier may have been admitted to accepting goods and undertaking to bring it to the designated place and handing it to the person addressed. Problems that arise are how the implementation of crude palm oil (CPO) transport contract, how are the rights and obligations of the parties in the crude palm oil (CPO) transport contract, and how to resolve disputes between PT. Mopoli Raya and PT. Mega Nusantara Abadi. The research method used in this thesis are normative juridicial research and supported by empiricial juridicial research. The data source were obtained by collecting primary data and secondary data. Primary data was obtained by interviewing the informants, while secondary data obtained through primary law material, secondary law material and tertiary law material. The data collection methods used in this thesis are document studies and interviews, then the data were analyzed qualitatively. Based on the results of this research, known that the implementation of the transport contract between PT. Mopoli Raya and PT. Mega Nusantara Abadi has been in accordance with the applicable provisions set forth in the crude palm oil transport letters Number SPK: 96 /MR-HK/MR/I/2016. PT. Mega Nusantara Abadi as the carrier is obliged to deliver crude palm oil (CPO) from PT. Mopoli Raya’s palm oil mill at Gedung Biara – Kuala Simpang to Belawan and Kuala Tanjung, and has the right to receive payment from PT Mopoli Raya for transporting crude palm oil (CPO), while PT. Mopoli Raya as the sender is obliged to pay for the transportation of crude palm oil as promised, and has the right of transportation to the destination safely. If any kind of disputes occur between PT. Mopoli Raya and PT. Mega Nusantara Abadi in respect of this contract, it shall be settled by deliberation, and if the agreement is not reached both parties have agreed to submit the dispute to The Medan District Court. Keywords : Agreement, Transportation, Crude Palm Oil